Multifactorial Vector of Regional Agriculture Development - Shepitko, Raisa Sergeyevna; Dugina, Tatiana Alexandrovna; Nemchenko, Alexander Vladimirovich; Likholetov, Yevgeniy Aleksandrovich (Economy of Regions, 2015)
The article reveals the agriculture development potential of the Volgograd region enabling to move to the stable type of reproduction as well as its factors: the natural conditions, location, technological types of production, agrarian structure, horizontal and vertical integration, state support. Methodological approach of the differentiation of green box subsidies is approved, the mechanism of its realization is proposed. The evidence base is substantiated by the long-term research of the soil intensification and soil quality factors influencing the soil productivity in the region. Within the boundaries of the existing natural areas, the following zones of territorial and economic development are allocated: the zones of competitive and efficient grain production; the zone of commercial sunflower production; the zones of territory and priority development. The criterion signs of their development are formulated. Alongside with the naturalfactor, the followingfactors were accepted as a criterion: the level of production adaptability and development of rural areas, displacement of population, customary lifestyle, arrangement of production infrastructure, resources, the structure of the agrarian economy. The evolutionary entrance of small agribusiness into the innovative economy have been reasoned as well as the creating on this basis of a special sector of agrarian economy - organic agriculture, which is reasonable to develop in the field of dairy cattle-breeding and vegetable-growing. A strategic analysis of the technological types of production existing in the regional agriculture in the context of organizational units and activities is presented. These are: industrial with innovative elements, extensive and intensive with innovative elements, extensive and intensive, extensive. They provide modernization as a factor of evolutionary formation of the innovative economy in the agrarian sector. Considering the global tendencies, the priorities of increasing the availability of agricultural mass producer in the market realized within a cluster, agricultural holding, cooperative are grounded.